Pengembangan Paket Wisata Tematik Berbasis Edukasi Lifeskill di Desa Cisaat, Kecamatan Ciater, Kabupaten Subang, Jawa Barat - lala siti sahara (Jurnal Abdimas Pariwisata, 2023)
Development of Thematic Tour Packages Based on Lifeskill Education in Cisaat Village, Ciater District, Subang Regency, West Java As a superior product of Cisaat Tourism Village, educational tourism needs to be modified in the form of other approaches to reach a broader market segmentation. The condition of the people of Cisaat Village, who have diverse livelihoods and daily activities and still promote local culture, allows the development of educational tourism based on life skills programs. According to UNESCO's version, the life skills program is prepared by referring to one of the pillars of education, namely, learn to be (learn to be someone). Mentoring activities are carried out with the target of participants being pokdarwis. The assistance forms include socialization, making tour packages, testing tour packages, mapping market segmentation, preparing tourism package promotion media, and monitoring and evaluation. Through this activity, it is hoped that the community can explore potential and develop existing attractions into a new tour package.